(untitled) (Swiss Medical Weekly, 2025)
Most people with diabetes mellitus operate motor vehicles safely without creating any meaningful risk on the road for themselves or others. A diagnosis of diabetes is, in itself, inadequate for determining a person’s driving capability or safety. Diabetes-related traffic accidents are rare for most drivers with diabetes mellitus and occur less frequently than for many other diseases that can impair driving performance and that are tolerated by society. The incidence of hypoglycaemia, which impairs the ability to drive, severe retinopathy (including macular oedema) or cataract formation affecting visual acuity required to drive a motor vehicle, and peripheral neuropathy, which can severely impair sensation in the feet, is not so common as to justify restricting driving privileges for all drivers with diabetes mellitus. In recent years, several pharmacological and technological innovations have revolutionised diabetes care. Continuous glucose monitoring system (CGMS) technology has only recently become increasingly integrated into diabetes therapy. Today, except for insulin, none of the treatments recommended for type 2 diabetes mellitus causes hypoglycaemia, and the risk of hypoglycaemia with ultra-long-acting insulins is lower. As a result, recommendations for driving motor vehicles have had to be adjusted. Since hypoglycaemia is the greatest risk factor for impaired driving ability, the latest technology (CGMS coupled with hybrid closed-loop insulin pumps) can reduce the number of hypoglycaemic events and blood glucose fluctuations. In addition, HbA1c and time in target range can be improved. Patients with type 1 diabetes mellitus are now, in exceptional cases, allowed to be licensed in higher vehicle categories. With the analysis of CGMS data, an objective assessment of the frequency of hypoglycaemia is now possible; this was previously only partially possible with blood glucose logs. Patients who are treated with insulin should use a CGMS. This also applies to gestational diabetes and diabetes during pregnancy. Since these systems warn of impending hypoglycaemia, they will also improve road safety, and the safety margin for blood glucose, previously set at 5 mmol/l, can be lowered to 4 mmol/l. For CGMS users, blood glucose measurements every 2 hours while driving are no longer necessary.